2011
DOI: 10.1007/s10165-011-0426-7
|View full text |Cite
|
Sign up to set email alerts
|

Recent trends in orthopedic surgery performed in Japan for rheumatoid arthritis

Abstract: The aim of this report was to review the use of orthopedic surgeries performed to manage rheumatoid arthritis (RA). Our review of studies published in English indicates that there has been a decrease in RA-associated surgeries in Western countries. Improvements in medical treatment may partly explain the reduction in numbers of orthopedic joint surgeries, which also suggests a worldwide trend toward improved long-term outcomes. However, the results of our multicenter study in Japan indicate that the number of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
0
11
0
1
Order By: Relevance
“…It is also necessary to expect the progression of deformities and evaluate rehabilitation and surgical treatment in patients who have already developed finger deformities. Momohara et al [15] reported that the total number of operations for RA decreased while joint reconstruction surgery of the upper extremities did not. This indicates the necessity for conservation of joint function and the level of patient requirements have been expanding.…”
Section: Discussionmentioning
confidence: 98%
“…It is also necessary to expect the progression of deformities and evaluate rehabilitation and surgical treatment in patients who have already developed finger deformities. Momohara et al [15] reported that the total number of operations for RA decreased while joint reconstruction surgery of the upper extremities did not. This indicates the necessity for conservation of joint function and the level of patient requirements have been expanding.…”
Section: Discussionmentioning
confidence: 98%
“…Similar conclusions were reached in a Finnish study [ 21 ]. Conversely, a multicenter study in Japan did not observe a decrease in the rates of RA-associated orthopedic surgery from 1998–2008, despite a steady increase in the proportion of patients using biologics from 2004 (1.8 %) to 2007 (10.0 %) [ 22 ]. One possible explanation for that finding is that in more recent years, patients who seek greater levels of activity may be undergoing joint surgery earlier than patients in the past.…”
Section: Discussionmentioning
confidence: 99%
“…However, in the study by Young et al, although the proportion of patients with RA among shoulder replacement recipients decreased, the absolute numbers of RA patients undergoing shoulder surgery looked as if they increased . In a study from Japan, Momohara et al reported an increase in finger arthroplasty surgery, whereas the number of elbow and wrist joint replacements remained constant from 1998 to 2008.…”
Section: Discussionmentioning
confidence: 97%
“…There are studies reporting decreases in upper limb joint replacements among patients with RA during recent decades, but in most studies, these changes started in the mid‐1990s before bDMARDs were available . Other studies suggest that no changes have occurred for rates of joint replacements among RA patients during recent decades .…”
Section: Introductionmentioning
confidence: 99%